Nonhomogeneous Boundary Value Problem for One-Dimensional Compressible Viscous Micropolar Fluid Model: Regularity of the Solution. (30th October 2008) - Mujaković, Nermina
Abstract : An initial-boundary value problem for 1D flow of a compressible viscous heat-conducting micropolar fluid is considered; the fluid is thermodynamically perfect and polytropic. Assuming that the initial data are Hölder continuous on] 0, 1 [ and transforming the original problem into homogeneous one, we prove that the state function is Hölder continuous on] 0, 1 [ × ] 0, T [, for eachT > 0 . The proof is based on a global-in-time existence theorem obtained in the previous research paper and on a theory of parabolic equations.